Roller crushers in iron mining, how does the degradation of Hadfield steel components occur?. (April 2021) - Varela, Luis Bernardo; Tressia, Gustavo; Masoumi, Mohammad; Bortoleto, Eleir Mundim; Regattieri, Cintia; Sinatora, Amilton
Highlights: The performance of the crusher steel component is a function of abrasion-impact process. Two wear/damage scales: micro- and macro scales were observed. Dynamic recrystallization on the working surface of the Hadfield steel was detected. Mechanical twinning was the main deformation mechanism. Crack propagation was observed trough with carbides at the grain boundaries. Cracks propagated along the grain boundaries related to the (1 1 1) orientation. Abstract: This work shows, for the first time, a systematic wear and damage analysis on a novelty roller crusher component used in the iron ore mining industry. Crusher suffers from complex abrasive-impact load during the comminuting the mineral ore in processing plants, which induce severe damage and defects that can result in a decreased performance or in a crusher breakage. The wear mechanisms and the extent of deformation have been studied by microhardness measurements, optical microscopy (OM), scanning electron microscopy (SEM) including electron backscattering diffraction (EBSD) and transmission electron microscopy (TEM). It was found that the abrasive-impact contact causes a significant hardness increment of over 700HV, around three times than initial state of the base material, and the strain hardening extends up to a depth in the extremely deformed region above 18 mm from the worn surface. SEM results of worn surfaces showed the impact and abrasion damages. Microstructure cross-section analyses exhibited the deformed microstructure is composed of bands and deformation twins. Also, it was observed the presence of crack propagated along with the large carbides at the grain boundaries. EBSD analysis of cracked and non-crack areas revealed that the high-distorted Taylor factor grains accompanied by grains oriented {1 1 1} parallel to the abrasive-impact dynamic load direction were susceptible to fatigue crack formation and propagation. Near to the cracks, a significant increase in dislocation density was found compared to other deformed regions, suggesting that these regions had a high level of stored energy resulting in an exhaust of the ability of plastic deformation. TEM results confirm the formation of nanoscale grains on the deformed surface layer.